2002
DOI: 10.1210/endo.143.3.8662
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Adipocyte Complement-Related Protein of 30 Kilodaltons by PPARγ Agonists: A Potential Mechanism of Insulin Sensitization

Abstract: Adipocyte complement-related protein of 30 kDa (Acrp30, adiponectin, or AdipoQ) is a fat-derived secreted protein that circulates in plasma. Adipose tissue expression of Acrp30 is lower in insulin-resistant states and it is implicated in the regulation of in vivo insulin sensitivity. Here we have characterized the ability of PPARgamma agonists to modulate Acrp30 expression. After chronic treatment of obese-diabetic (db/db) mice with PPARgamma agonists (11 d), mean plasma Acrp30 protein levels increased (>3x). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(94 citation statements)
references
References 34 publications
5
82
0
7
Order By: Relevance
“…Recent studies have demonstrated that treatment with TZDs increases plasma adiponectin levels in type 2 diabetic patients [18][19][20][21] and murine models of obesity and type 2 diabetes, db/db mice [22], and even in nondiabetic subjects [21,22]. Moreover, treatment with a TZD, rosiglitazone, has been shown to increase adiponectin mRNA and protein expression in adipose tissue of db/ db mice [22]. Therefore, TZDs are likely to enhance adiponectin synthesis and secretion in adipose tissue and subsequently increase plasma adiponectin levels.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that treatment with TZDs increases plasma adiponectin levels in type 2 diabetic patients [18][19][20][21] and murine models of obesity and type 2 diabetes, db/db mice [22], and even in nondiabetic subjects [21,22]. Moreover, treatment with a TZD, rosiglitazone, has been shown to increase adiponectin mRNA and protein expression in adipose tissue of db/ db mice [22]. Therefore, TZDs are likely to enhance adiponectin synthesis and secretion in adipose tissue and subsequently increase plasma adiponectin levels.…”
mentioning
confidence: 99%
“…Plasma apo C-III and adiponectin are biomarkers of PPARα (20,21) and PPARγ (15,22) activation, respectively. Two weeks of treatment with E3030 significantly reduced plasma apo C-III levels at 0.1 mg / kg or greater (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The four methanolic extracts had a great amount of flavonoid compounds which did not alter the low level of insulin [29].This means that the reducing effect of methanol extracts (flovonoid compunds) on blood glucose of diabetic animals was not related to the insulin content in blood. Flavonoids ingestien into diabetic animals increased blood adiponectin level, which produced a hypoglycemic action of insulin sensitivity [29,30,31,29]. Similarly, it is believed that the presence of flavone glycosidic components in the plant extract of Anastatia hierochuntia [32] is responsible for reducing the blood glucose level in STZ-diabetic rats.…”
Section: Discusionmentioning
confidence: 99%